(untitled) (Web of Teachers: Inderscience Research, 2025)
This article on the topic of musical-analytical analysis of Tanbur and Dutor instruments analyzes the historical formation, structure and musical possibilities of the ancient stringed instruments of the peoples of Central Asia – tanbur and dutor. The article examines the performance techniques, aesthetic characteristics of instruments and their role in musical ensembles. The article also covers the role of tanbur and dutor in creating musical images that are given in harmony. According to the results of the analysis, these instruments are manifested as an important tool of aesthetic and cultural value in folk music and status art.